Influence of Anode Diffusion Layer on the Performance of a Passive Direct Ethanol Fuel Cell - Ekdharmasuit, Panuwat (Trends in Sciences, 2024)
One of the main challenges with passive direct ethanol fuel cells (DEFCs) is ethanol transport management since the liquid ethanol is supplied to the anode compartment by natural processes including convection and diffusion with a low cell operating condition. The significant layer in the cell is the diffusion layer (DL), which facilitates reactants to reach the anode catalyst layer (CL). In this study, the impact of various DLs fabricated of readily accessible commercial materials on cell performance in passive DEFCs with different ethanol feed concentrations was examined with various in-situ characterization methods. The results demonstrate that the cell with a DL coated by the hydrophobic microporous layer (MPL) yielded the best performance of 0.887 mW·cm-2 at the optimal ethanol feed concentration of 5 M. In conclusion, the benefits of enhancing ethanol mass transfer to the anode CL would outweigh the drawbacks of preventing ethanol crossover to the cathode. HIGHLIGHTS The effect of the anode diffusion layer (DL) on passive direct ethanol fuel cell (DEFC) performance was determined Five different anode DLs fabricated of readily accessible commercial materials were employed Various characterizations enabled the assessment of each loss affecting the passive DEFC performance The cell with an anode DL modified with a hydrophobic microporous layer (MPL) exhibited the best cell performance The optimal ethanol feed concentration of the best cell was found to be 5 M GRAPHICAL ABSTRACT